Defining and assessing disability under U.S. social security law from a comparative perspective - Clark, Susan [Verfasser] (My University, 1992)
"The United States and Germany generally view disability under their respective social security schemes as a prolonged or permanent physical or mental impairment which causes a decrease in earning capacity or an inability to work. Despite this agreement on the basic concept, U.S. and German law differ significantly in the definition and determination of disability. Germany defines the risk more broadly to include two distinct types or degrees of disability and to allow for alternative measures of the ability to work. The United States, by comparison, has one, all-or-nothing test of disability: a medically determinable impairment must result in an inability to perform any substantial gainful activity found in the U.S. economy. Substantial gainful activity is defined currently as work with earnings of 500 Dollar or more a month; there is no alternative to this amount and no provision is made for degrees of disability, including occupational disability. The U.S. definition of disability is also more restrictive than its German counterpart in that it specifically requires an impairment to have an expected duration of at least twelve month or to be considered fatal." (author's abstract) ((en)) In dem Beitrag werden die deutschen und US-amerikanischen Definitionen der Begriffe Invalidität und Berufsunfähigkeit vorgestellt und die Rechtsfrage verglichen. (IAB)
Keywords: P 1.6 Behinderte; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; Invalidität; Hochqualifizierter; Technischer Beruf; Internationaler Vergleich; Quantitative Angaben